INOVASI PEYANAN PEMBUATAN PASPOR PADA AKHIR PEKAN MELALUI GERAI PASPOR TANGCITY (GESIT) DI TANGCITY MALL - Jumiati, Siti; Yusuf, Yusmedi; Firdiyani, Fitria (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
This study aims to determine the innovation of passport making services on weekends through the Tangcity Passport Outlet (GESIT) at Tangcity Mall created by the Class I Non TPI Tangerang Immigration Office as an assistance to people who have difficulty making passports on weekdays. The research method uses a descriptive qualitative method with data collection techniques through observation, interviews and documentation. The theory in this study uses the best practice theory regarding the success of the implementation of innovation proposed by Prasojo. The results of the study indicate that the innovation of weekend making services through the Tangcity Passport Outlet (GESIT) has been successfully implemented in accordance with the criteria for the success of innovation proposed by Prasojo, seen from the positive impacts generated for improving people's living conditions, based on partnerships with integrity, becoming an effective solution to the problem of passport demand in the Tangerang area, led by an inspiring and responsive leadership style, ensuring that all people get the services they need, and showing high transferability to be replicated by other regions. However, there are still several obstacles, which are opportunities to further improve the innovation of the Tangcity Passport Outlet (GESIT), including increasing the passport quota and improving the facilities and infrastructure provided.